Exploiting enzyme promiscuity to shape plant specialized metabolism. (31st January 2019) - Kreis, Wolfgang; Munkert, Jennifer
Abstract : We review concepts in the evolution of adaptive pathways in plant specialized metabolism, with a focus on enzyme promiscuity and how this may lead to 'new' metabolic pathways. Abstract: The amazing variability of plant metabolism and its rapid divergence during evolution pose fundamental questions as to the driving forces, mechanisms, and players in metabolic differentiation. This review examines concepts that help us understand adaptive pathway evolution, with a particular emphasis on plant specialized metabolism, previously often termed secondary metabolism. Following a general introduction to pathway and metabolite evolution, the focus is directed to enzyme promiscuity and its classification. Promiscuous enzymes (or substrates), 'silent' elements of the metabolome, and the 'underground metabolism' may be used and combined to evolve 'new' metabolic pathways. It appears that new pathways rarely appear from scratch, but instead emerge from 'floppy' enzymes and elements of a 'messy' metabolism, and in this way a range of metabolites is generated, some of which may provide benefits to the plant.